Managing responsibly : alternative approaches to corporate management and governance - Buckingham, Jane; Nilakant, V., 1952- (Corporate social responsibility series., 2012)
Bringing together the thoughts of scholars, looking for alternatives to the self-interest maximization so characteristic of existing corporate governance, 'Managing Responsibly' explores the limitations of the thinking that dominates Western corporate and business culture. Contributors draw on non-Western traditions and experience to suggest workable inter-cultural models that can enhance organizational effectiveness and help to avoid damage to and exploitation of communities and the environment.